Mycobacterium tuberculosis PPE68 and Rv2626c genes contribute to the host cell necrosis and bacterial escape from macrophages - Danelishvili, Lia (Virulence, 2015)
Alveolar macrophages are the main line of innate immune response against M. tuberculosis (Mtb) infection. However, these cells serve as the major intracellular niche for Mtb enhancing its survival, replication and, later on, cell-to-cell spread. Mtb-associated cytotoxicity of macrophages has been well documented, but limited information exists about mechanisms by which the pathogen induces cell necrosis. To identify virulence factors involved in the induction of necrosis, we screened 5,000 transposon mutants of Mtb for clones that failed to promote the host cell necrosis in a similar manner as the wild-type bacterium. Five Mtb mutants were identified as potential candidates inducing significantly lower levels of THP-1 cell damage in contrast to the H37Rv wild-type infection. Reduced levels of the cell damage by necrosis deficient mutants (NDMs) were also associated with delayed damage of mitochondrial membrane permeability when compared with the wild-type infection over time. Two knockout mutants of the Rv3873 gene, encoding a cell wall PPE68 protein of RD1 region, were identified out of 5 NDMs. Further investigation lead to the observation that PPE68 protein interacts and exports several unknown or known surface/secreted proteins, among them Rv2626c is associated with the host cell necrosis. When the Rv2626c gene is deleted from the genome of Mtb, the bacterium displays significantly less necrosis in THP-1 cells and, conversely, the overexpression of Rv2626c promotes the host cell necrosis at early time points of infections in contrast to the wild-type strain.